Arabization of Sports Terms on the Emarat Al-Yaoum Website - Abdul Jabbar Siddiq Syah; Mugy Nugraha (Litteratura: Jurnal Bahasa dan Sastra, 2024)
Sports are more than just games; they have become a platform for building bilateral relationships. Many sports have gained international prominence and entered the Arab world, such as the Qatar World Cup and others, leading to the absorption of foreign sports terminology into the Arabic language. This study aims to identify the Arabization (ta'rib) rules used by the news website "Emarat Al-Yaum" in its sports section when adapting foreign words into Arabic. The research data was collected from sports news published in March 2023 on the Emarat Al-Yaum website. The study employs a descriptive qualitative research method, involving the analysis of news articles and the collection of Arabized sports terms. The findings reveal that the "Emarat Al-Yaum" news website extensively covers international sports news, resulting in the adoption of numerous sports-related loanwords. In terms of Arabization, the website largely adheres to the standardization rules set by the Arabic Language Academy (Majma' Lughah Arabiyah) in Cairo for converting Latin letters into Arabic. For example, the letter 'C' is replaced with (ك) in words like "acrobatic," and 'P' is replaced with (ب) in words such as "Polo" and "Protein."However, the study also notes some deviations from the Cairo Arabic Language Academy's guidelines, such as the treatment of the 'Ng' sound and the representation of 'Q' with (ق). The ta'rib rules employed by Emarat Al-Yaum include vowel changes, letter substitutions, additions, and omissions when adapting foreign words.